“Page priority” does not exist in the Code: Neomegalotomus parvus (Westwood, 1842) has precedence over Neomegalotomus simplex (Westwood, 1842) (Hemiptera, Heteroptera, Alydidae) - Nemésio, André (Zootaxa, 2007)
In a recent paper, Schaefer (2007) considered Neomegalotomus simplex (Westwood, 1842: 18) and Neomegalotomus parvus (Westwood, 1842: 19) (Hemiptera: Alydidae) as subjective synonyms – although no specific reason for this was given, except the following statement, after commenting he had seen both types: “I find that N. parvus and N. simplex are the same species, and synonymize them here” (Schaefer 2007: 320). Nevertheless, Schaefer (2007) explicitly invoked a non-existent rule under the International Code of Zoological Nomenclature (hereafter referred to as the Code) to justify his choice of N. simplex as senior synonym (because both names were published in the same work): “by page priority, Neomegalotomus simplex has seniority over N. parvus” (Schaefer 2007: 320). The above interpretation is wrong according to the Code. There is no “page priority” in any article of the Code. When two or more names, spellings, or nomenclatural acts are published on the same date, priority among them, according to the Code, is given either by date or by First Reviser action, not by page number (Articles 24.2.1 and 24.2.2). The only mention to a “page priority” in the Code is Recommendation 69A.10, in Article 69.4, which deals with fixation of type species. This recommendation (the last one in a rank series of 10) states that “all other things being equal, preference should be given to the nominal species cited first in the work, page or line (‘position preference’).” Nonetheless, it does not deal with seniority of synonyms, homonyms, spellings or nomenclatural acts.